Primary Pancreas Sarcoma, Optimal Treatment and Prognostic Factors - Nasrolahi, Hamid; Omidvari, Shapour; Kadkhodaei, Behnam; Hamedi, Seyed Hasan; Ahmadloo, Niloofar; Ansari, Mansour; Mohammadianpanah, Mohammad; Mosalaei, Ahmad (Reports of Radiotherapy and Oncology, 2015)
Context: Sarcoma is a rare human cancer and pancreatic sarcoma is even rarer. Its treatment and clinical history and prognosis are not well described. Evidence Acquisition: In this review, we collected all articles in the English language found in PubMed that were published between January 2000 to August 2015 to draw conclusions. We found 170 articles in total and 124 articles were excluded. The remaining 46 reports and information of 55 patients were collected and analyzed. Results: Mean age was 57.1 ± 16.7 years and male/female ratio was 27/28. The most common presenting symptom was pain. In 31 cases no adjuvant treatment was prescribed. Others received different chemotherapy agents and only two cases received radiotherapy. Mean tumor size was 9.0 ± 6.8 cm (1 - 27 cm) and the most common type was leiomyosarcoma (16 patients). Nine patients had carcinosarcoma and six cases had MFH. The most common site of metastasis was liver, 14 patients had liver metastasis at presentation. Median survival was 14 months. One, three and five year overall survival were 78.4, 48.5 and 48.5 percent, respectively. We found no effective clinical factor in survival. Conclusions: Pancreatic sarcoma is a rare disease and an optimal treatment, such as surgery, chemotherapy or radiotherapy is not well defined.